Comparative effectiveness of natural by-products and synthetic sorbents in oil spill booms. (1st November 2018) - Pagnucco, Rebecca; Phillips, Megan L.
Abstract: Sorbent booms are considered a 'first line of defence' technology used for containing and minimizing the impacts of crude oil spills. Booms containing human hair waste as sorbent were compared to other natural sorbents, including cotton by-product, recycled cellulose, as well as booms containing synthetic polypropylene, in order to evaluate their effectiveness in adsorbing petroleum crude oil pollution, remaining buoyant, and adsorbing seawater. A series of oceanic mesocosm experiments were used to simulate oil spill pollution events and to test sorbent effectiveness. Hair by-product was found to be significantly better at adsorbing crude oil on average (i.e. 0.84 g of crude oil per 1 g of sorbent) than all other materials, although it had wider variation in adsorbency likely associated with the non-homogeneous nature of mixed human hair. Hair sorbent was also observed to be less naturally buoyant than other materials, potentially due to low surface tension or increased porosity. Graphical abstract: Highlights: Hair adsorbs more crude oil (per g of sorbent) compared to other tested materials. Polypropylene booms had the highest oil adsorbency ratio, followed by hair. Hair is less buoyant and should be paired with floatation devices or socking.